Utilização de um resíduo de caulim da Amazônia na síntese da zeólita ferrierita - GONÇALVES, Angelina Lobato (2019)
The constant search for environmentally sound and economically viable processes has driven several research segments in recent years. The main problem today is finding alternative raw materials, which give industrial processes greater profitability and a lower impact on the environment. Therefore, the objective of this research was the use of a residue from the processing of kaolin in the Amazon, to synthesize a ferrierite type zeolite. This zeolite is widely used in the petrochemical industry because it has relevant catalytic properties. The use of a reject in the synthesis of this zeolite is of paramount importance, since besides transforming a material of low commercial value into a product of high added value, it still reduces the impacts generated by the storage of the same one. Another important aspect is that zeolite ferrierite had not yet been synthesized from a residue, which demonstrates the relevance of this study. The techniques of X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the starting materials and the products formed, the chemical analysis was also used to characterize the starting materials. The synthesis methodology used is in agreement with that established by IZA, however some parameters were varied: hydrothermal treatment time, synthesis temperature, and alternative source of aluminum and partially silicon, the residue of kaolin. First the residue was calcined at 700°C/2 h to obtain the metakaolin, then the silica was aged on an orbital shaker at 80 rpm for 24 h and with 15 ml of H2O in a teflon beaker, after aging, the remaining reactants: metakaolin, NaOH in micro-beads and ethylenediamine, the teflon beaker was placed inside the stainless steel reactor, and it was placed in a greenhouse for the hydrothermal process at 180ºC, the synthesis times being varied by 12, 24, 48 and 72 hours. Finally the material was filtered to a neutral pH (between 7 and 8), oven dried for 2h at 180°C and calcined in Mufla for 17h at 540°C, with a heating rate (TA) of 9°C/min. The results of the analysis of the formed products showed that zeolite ferrierite was synthesized only in times of 24 and 48 hours, indicating the time of 24 hours as the most suitable for the formation of this material. This work also analyzed the influence of the aging stages of the silica and the calcination of the formed products. At the time these steps were withdrawn from the process, there was a decrease in ferrierite crystallization. Thus, these steps were essential for the synthesis of ferrierite.